Sufistic Literature from Pesantren: (Textual Studies in the Syi’ir Taqwa Manuscript by KH. Abdul Hadi Langitan) - Wasid, Wasid; Rochimah, Rochimah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article will examine the Sufistic Literature of Islamic boarding schools with the manuscript of the book Shi’ir Taqwa by KH. Abdul Hadi Langitan Tuban as a study material. For this reason, this article will answer two formulations. First, what is the context of the Sufistic literature of the book Shi’ir Taqwa by KH. Abdul Hadi? Second, how are the Sufistic values in the book of Shi’ir Taqwa by KH. Abdul Hadi is related to human nature? This study uses a philological approach with a focus on the textology of the Shi’ir Taqwa manuscript with a focus on its content and content. In addition, this study also uses a sociology approach of knowledge in order to find the relationship between the Shi’ir Taqwa manuscript and its author, considering that no text is born in a vacuum. From the study, the author concluded; first, the Sufistic literary context of the book Shi’ir Taqwa is the work of KH. Abdul Hadi has a close relationship with the dynamics of Sufism knowledge that develops in the world of Pesantren in this case the Langitan Pesantren. The use of the Javanese pegon language also illustrates that the culture of the pesantren is very strongly related to its community. Second, in substance, Shi’ir Taqwa contains advice that contains the values of moral Sufism. This advice in Sufistic literature leads the process of forming Sufistic reasoning of readers and listeners to continue to be immersed in the values and practices of Sufism.